Size-dependent aggression towards kin in a cannibalistic species. (25th March 2022) - Fouilloux, Chloe A; Fromhage, Lutz; Valkonen, Janne K; Rojas, Bibiana
Abstract: In juveniles extreme intraspecies aggression can seem counter-intuitive, as it might endanger their developmental goal of surviving until reproductive stage. Ultimately, aggression can be vital for survival, although the factors (e.g., genetic or environmental) leading to the expression and intensity of this behavior vary across taxa. Attacking (and sometimes killing) related individuals may reduce inclusive fitness; as a solution to this problem, some species exhibit kin discrimination and preferentially attack unrelated individuals. Here, we used both experimental and modeling approaches to consider how physical traits (e.g., size in relation to opponent) and genetic relatedness mediate aggression in dyads of cannibalistic Dendrobates tinctorius tadpoles. We paired full-sibling, half-sibling, and non-sibling tadpoles of different sizes together in an arena and recorded their aggression and activity. We found that the interaction between relative size and relatedness predicts aggressive behavior: large individuals in non-sibling dyads are significantly more aggressive than large individuals in sibling dyads. Unexpectedly, although siblings tended to attack less overall, in size-mismatched pairs they attacked faster than in non-sibling treatments. Using a theoretical model to complement these empirical findings, we propose that larval aggression reflects a balance between relatedness and size where individuals trade-off their own fitness with that of their relatives. Lay SummaryBefore you eat someone, you have to attack them first. Here, we investigated the factors that shape aggression in the cannibalistic tadpoles of the dyeing poison frog. We find that aggression depends on both size and relatedness: when set in pairs, large tadpoles are half as aggressive towards their smaller siblings than to nonsibs. It looks like belonging to the same family provides some protection against aggression, though no one is ever truly safe.